What is the Gold Standard for Advanced Hallux Rigidus? Minimum 10 Year Follow-Up Comparison of Interposition Arthroplasty and Arthrodesis Shows Similar Outcomes - Jeffrey E. Johnson MD, FAAOS; Andrea R. Phinney MD; Mary Hastings PT, DPT, MSCI, ATC; Hyo Jung Jeong PT, PhD, MS; Ling Chen; Andrew P. Thome MD; Jeremy J. McCormick MD, FAAOS; Jonathon D. Backus MD FAAOS (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Other Introduction/ Purpose: Hallux rigidus is characterized by arthritic changes of the first metatarsophalangeal joint (MTPJ) with joint space narrowing, osteophyte formation, and painful MTPJ motion. Although MTPJ arthrodesis is considered the “gold standard,” a Modified Oblique Keller Capsular Interposition Arthroplasty (MOKCIA) is an alternative treatment for hallux rigidus in patients who desire to retain MTPJ motion. The purpose of this study is to compare long-term outcomes (patient satisfaction, radiographic alignment, MTPJ walking kinematics, and plantar pressure) between the MOKCIA and 1st MTPJ arthrodesis. We hypothesized that patients undergoing MOKCIA will retain motion, but when compared to Arthrodesis at long-term follow-up, some MOKCIA patients may develop abnormal forefoot loading, toe malalignment and need revision. Methods: 26 patients who underwent a MOKCIA (n=14, 74±7 years old, 9 female, average 15 years from surgery) or an arthrodesis (n=12, 70±4 years old, 6 female, average 13 years from surgery) were recruited from a retrospective chart review (January 1, 2005, and December 31, 2018). Study measures included 11-point visual analog scale (VAS) Pain and satisfaction, Foot and Ankle Assessment Measure (FAAM) and PROMIS physical function scores, weight bearing radiographs (MTPJ valgus and 1st proximal phalanx to ground sagittal), walking MTPJ (first phalanx relative to forefoot) sagittal plane kinematics, forefoot and 1st toe peak plantar pressure during walking, MTPJ goniometer range of motion, and number of additional 1st MTPJ surgical interventions required. Two-sample t-tests or Chi-square were used to compare groups. Results: Groups did not differ on demographic characteristic or patient reported outcomes [VAS Pain (MOKCIA=0.1±0.3, Arthrodesis=1.2±1.8, p=0.06), satisfaction (MOKCIA=9.4±0.9, Arthrodesis=8.3±1.6, p=0.054), FAAM (MOKCIA=94±9, Arthrodesis=95±7, p=0.65), PROMIS (MOKCIA=50±6, Arthrodesis=48±6, p=0.41)]. MTPJ valgus was increased in the Arthrodesis group (MOKCIA=4±5°, Arthrodesis=7±4°, p=0.05). First phalanx to ground was more plantarflexed in the MOKCIA group (MOKCIA=9±7°, Arthrodesis=1±7°, p=0.01)]. Walking MTPJ excursion was greater in the MOKCIA group (MOKCIA=25±9°, Arthrodesis=13±8°, p< 0.001). There was no group difference in forefoot and 1st toe walking peak plantar pressure (Forefoot: MOKCIA=111±29 N/cm 2 , Arthrodesis=127±22 N/cm 2 , p=0.12 and Toe: MOKCIA=77±28 N/cm 2 , Arthrodesis=101±41 N/cm 2 , p=0.10). MTPJ extension range of motion was greater in the MOKCIA group (MOKCIA=48°±13, Arthrodesis=25°±8, p< 0.001). One person in the Arthrodesis group required hardware removal, but no MOKCIA patient required additional surgery. Conclusion: More than 10 years of follow-up after surgery, patients in both MOKCIA and Arthrodesis groups had little pain, were similarly satisfied, and reported high function with little limitation due to their toe surgery. Radiograph alignment showed no progressive deformity in the MOKCIA group and patients were able to retain MTPJ extension range of motion during walking. Plantar pressures were not impacted by surgical intervention. No MOKCIA patient required revision. These results suggest MOKCIA is a reasonable alternative option compared to first MTPJ arthrodesis for long term treatment of hallux rigidus in patients who desire to preserve toe range of motion.